Symmetric Lipomatosis Arising in the Tongue Presenting as Macroglossia and Articulatory Disorder - Masanori Kudoh; Ken Omura; Arata Satsukawa; Koshi Matsumoto; Takahide Taguchi; Hiroyuki Harada; Yoshimasa Ishii (Case Reports in Otolaryngology)
Symmetric lipomatosis is definitively characterized by symmetric, tumorous lipomatous proliferation of adipose tissue that often develops in the head and neck, shoulders, and upper trunk. However, in the oral region, symmetric lipomatosis of the tongue (SLT) is an extremely rare condition related to generalized lipidosis that is often caused by chronic alcoholism. It is characterized by multiple symmetric lipomatous nodules and diffuse bilateral swelling located within the tongue. We report an extremely rare case of SLT arising in an 80-year-old man with a long history of alcoholic liver cirrhosis. He exhibited multiple soft nodular protrusions on the bilateral margin of the tongue presenting as macroglossia for years. Although MR imaging showed multiple fatty masses on both sides of the tongue, there was no elevated tumor mass on the bilateral margin. The patient underwent bilateral partial glossectomy under general anesthesia. Histopathologically, the resected tumor exhibited diffuse infiltration with mature adipose tissue lacking a fibrous capsule. Due to the lipidosis and the unusual presentation of multiple lesions, the lesion was ultimately diagnosed as SLT. At present, after surgery, the patient wears a full-denture and is in excellent condition, with no sign of recurrence, improved QOL, and recovery of masticatory, articulatory, and speech intelligibility functions.